Kinetic study of neodymium oxide chlorination - Bosco, Marta Verónica (2012)
The kinetics of the chlorination of neodymium oxide has been investigated by thermogravimetry between 312 ºC and 475 ºC and for partial pressures of chlorine ranging from 10 to 50 kPa. The starting temperature for the reaction of neodymium oxide with chlorine is determined to be about 250 ºC leading neodymium oxychloride as product. The results showed that for temperatures below 425 ºC the system is under chemical control and the formation of the oxychloride progresses though a nucleation and growth mechanism. The influence of chlorine mass transport through the bulk gas phase and through the boundary layer in the overall rate was analyzed. In the absence of these two mass-transfer steps, a reaction order of 0.40 with respect to chlorine partial pressure, and activation energy of 161 ± 4 kJ mol-1 were determined. A complete rate expression has been successfully developed.